6x-2(x-2)=9x+4

Simple and best practice solution for 6x-2(x-2)=9x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2(x-2)=9x+4 equation:


Simplifying
6x + -2(x + -2) = 9x + 4

Reorder the terms:
6x + -2(-2 + x) = 9x + 4
6x + (-2 * -2 + x * -2) = 9x + 4
6x + (4 + -2x) = 9x + 4

Reorder the terms:
4 + 6x + -2x = 9x + 4

Combine like terms: 6x + -2x = 4x
4 + 4x = 9x + 4

Reorder the terms:
4 + 4x = 4 + 9x

Add '-4' to each side of the equation.
4 + -4 + 4x = 4 + -4 + 9x

Combine like terms: 4 + -4 = 0
0 + 4x = 4 + -4 + 9x
4x = 4 + -4 + 9x

Combine like terms: 4 + -4 = 0
4x = 0 + 9x
4x = 9x

Solving
4x = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
4x + -9x = 9x + -9x

Combine like terms: 4x + -9x = -5x
-5x = 9x + -9x

Combine like terms: 9x + -9x = 0
-5x = 0

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| (-2)x=-5 | | 6a^2-13a+5=0 | | -3.8d=8.74-1.9d | | x-(-6)=-80 | | 10(n-2)=100 | | -22=r+3+4r | | [4u-2]=10 | | -17=-5a+7-4 | | 3(9-7)=2(10+9) | | 55-4x=8x+22 | | 5g+4(-5+3g)=1-9 | | x-41=-58 | | 6x-5=-8X-2 | | -4=5+2n-1 | | 3a+30=6a | | 4(20-n)=4 | | x^2+5-3x=0 | | 15k-3=4+6k | | 12x=4(7+24) | | 20a^2+5a=0 | | -12x=4(7+24) | | 2+2x=x+14 | | 8=3(3c+5) | | 16k+35= | | 5(n+1)+10=20 | | 6y-3=6y+18 | | 3x+4=x+24 | | -22=7(1+3v)-8 | | .5a-9=4a+5 | | 5(n+2)=30 | | 5g-15=3(-5) | | 0.02+0.01=0.005 |

Equations solver categories